Contribuições ao acionamento e controle dos motores de relutância variável e síncrono de relutância - Scalcon, Filipe Pinarello (2019)
This master thesis presents contributions to the driving and control of switched reluctance motors and synchronous reluctance motors. The main characteristics of the switched reluctance machine are the low production costs, robustness, fault tolerance, high starting torque and absence of magnets or windings in the rotor. These characteristics make the SRM a candidate for aerospace and electric vehicle applications. The synchronous reluctance machine has as its main characteristics low production costs, robustness and absence of magnets or windings in the rotor. These characteristics, coupled with its similarity to the induction machine, make it an alternative for industry applications. Thus, for both machines, it is necessary to regulate rotor speed. In this context, rotor speed control strategies are proposed for both machines. Two techniques are presented for the switched reluctance motor: a sliding mode algorithm, where the design and stability analysis of the controller are presented, and a robust model reference adaptive control, where the design and the choice of the reference model are shown. or the synchronous reluctance machine, PI controllers are used, where the method for designing the gains is discussed. The constructive characteristics, driving strategies and mathematical modeling of each machine are shown. Simulation and experimental results validate the theoretical analysis developed and demonstrate the performance of the proposed control schemes.